Glucocorticoid treatment for primary and secondary central nervous system vasculitis - Uslu, Emine (Acta Medica, 2024)
Although the first-line treatment of central nervous system vasculitis (CNSV) is glucocorticoids (GC), the duration and dose of GC is still unknown. Although CNSVs seem to be a disease limited to a single area, they are a heterogeneous group of diseases clinically, in terms of involvement pattern and course. Due to the highly heterogeneous nature of the disease, patient-specific determination of the initial dose of GC is essential. Considering the disease courses, it may be more appropriate to consider 1mg/kg oral GC treatment if small/distal vessels are involved and intravenous bolus GC treatment if large/proximal vessels are involved in primary-CNSVs. In secondary-CNSVs (Anca-associated vasculitis, Behçet’s syndrome, Systemic Lupus Erythematosus) intravenous high dose GC treatment is recommended.